Faktor Penentu Kesediaan Petani Krisan Membayar Iuran Pengairan - Mithaqul Risnitasari; Ati Kusmiati; Ahmad Zainuddin; Cindera Rosa Damaiscena (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
The limited irrigation infrastructure required farmers to take turns using water. Farmers realized the importance of water availability in chrysanthemum cultivation, prompting them to seek alternative irrigation sources to meet the needs of their chrysanthemum crops. The purpose of this study was to estimate the farmers’ willingness to pay for irrigation service fees in Kampung Krisan and to identify the factors that influenced it. The sampling method used saturated sampling with a sample of 30 respondents (chrysanthemum farmers from the Sidorejo IV Farmer Group). The analyses applied in this study were the Contingent Valuation Method and multiple linear regression analysis. The results of the study showed that all respondents expressed a willingness to pay the irrigation fee. The average value of respondents’ Willingness to Pay (WTP) was IDR 208,333 per month, with a total WTP value of IDR 187,500,000 per month. The variables that significantly influenced the WTP value were land area, income, and water needs cost. Meanwhile, variables such as age, length of education, number of family members, distance from the land to the water source, and knowledge of irrigation fee functions had no significant effect on the farmers’ willingness to pay for irrigation services in chrysanthemum cultivation.